Rethinking Black motherhood and drug addictions: counternarratives of Black family resilience - Tivis, Tierra B. (Black studies & critical thinking, 2018)
"These people are suffering": help versus incarceration -- Tools for understanding drug addiction and black mothers' standpoint -- Origin of the crack ho': Mammies, Jezebels, controlled images, and prosecution of addiction -- "From suga to shit": the drug business and destruction of black communities -- More about the mothers, research practice, black motherhood and addiction -- "I had help": kinship, drug addictions, and black family resilience -- "Wasn' no junkie, I was a workin' addict--it's a difference": self- definition of black mothers' roles and responsibilities -- Crack baby aftermath and navigating educational institutions -- "I was just cryin' out to God": recovery and the spirituality of struggle